PREVENTION OF COMPLICATIONS OF PHYSIOLOGICAL STIMULATION OF OVARIES IN WOMEN WITH ANOVULATION - Kurbaniyazova , M.Z.; Saparbayeva, N.R. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The study found that an increase in the concentration of estradiol after the administration of hCG can be used as a predictor of the development of ovarian hyperstimulation syndrome (OHSS). Therapy with cabergoline effectively prevents OHSS, and the use of a double ovulation trigger significantly eliminates its development compared to monostimulation with hCG.